Bransford & Stein Theory: Mathematical thinking Process of Prospective Mathematics Teacher Students in Solving Statistical Problems Based on Cognitive Learning Style - Herlina, Sari; Wahyuni, Reni; Julianti, Dola; Novianti, Andini (PRISMA, 2024)
A good mathematical thinking process for prospective students, mathematics teachers is a necessity that needs to be had. The purpose of this study is to describe the profile of the mathematical thinking process of prospective mathematics teacher students based on Field Dependent and Field Independent learning styles in solving mathematical problems. The method of research is descriptive-qualitative research. The research subjects taken were 3 mathematics education students for Field Dependent type learning styles and 3 people for Field Independent types. Data collection techniques, namely: tests of mathematical thinking skills on statistical material, and interviews. Data analysis uses stages, namely: (1) data reduction; (2) present data based on Bransford & Stein Theory; (3) make conclusions. The results showed that the mathematical thinking process of prospective mathematics teacher students is 1) The field of independent learning style is more systematic in reading story problems, able to identify important information and classify it into mathematical models / variables. While field-dependent students tend to read questions globally and focus less on details; 2) in understanding the problem, FI students more quickly map the problem into relevant mathematical representations. FD students think deductively and need concrete examples to understand problems; 3) FI students are more creative and flexible in developing problem-solving strategies using various mathematical concepts and procedures. FD students more often use the standard strategies that have been taught. 4) FI students are meticulous and detailed in interpreting solutions back to the context of the original problem. FD students tend to focus on the end result without relating to the meaning of the problem.